Primary intra-ventricular hemorrhage in 33-year-old man: a case report - Gunawan, Stephanie E.; Putri, Setyawati Asih (International Journal of Advances in Medicine, 2022)
The aim of the study was to provide insight into cases of primary intra-ventricular hemorrhage caused by arterial venous malformations. A 33-year-old man visited the emergency room and admitted that he had a chief complaint of headache for the last 7 days. Neurological clinical examination only found nuchal rigidity. The CT scan of the head showed intra-ventricular hemorrhage and the CTA results showed an AVM with a left occipital nidus with arterialization of the posterior cerebral artery. One day before the DSA was performed, the patient had a seizure and based on a repeat CT scan, the bleeding spread to the parenchyma. The patient refused decompression and decided to go home after his condition stabilized and his complaints improved with anti-edema treatment. A repeat DSA action was planned but the patient had financial problems. Primary intra-ventricular hemorrhage occurs when the nidus arterial venous malformation is adjacent to the ventricle although this is only 7% of all cases of primary intra-ventricular hemorrhage. In the case of primary intra-ventricular hemorrhage, complications need to be wary of when hydrocephalus appears. In addition, digital subtraction angiography should be performed prior to endovascular surgery as the main modality of therapy. Arterial venous malformation can be one of the causes. Digital angiography and Endovascular measures should be performed in this patient to prevent further complications. However, the refusal of the patient and family until the time of this case report was made is a separate obstacle in the diagnostic and therapeutic process.